2020
DOI: 10.1016/j.waojou.2020.100454
|View full text |Cite
|
Sign up to set email alerts
|

Does hereditary angioedema make COVID-19 worse?

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has spread rapidly worldwide. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent for COVID-19, enters host cells via angiotensin-converting enzyme 2 (ACE2) and depletes ACE2, which is necessary for bradykinin metabolism. The depletion of ACE2 results in the accumulation of des-Arg (9)-bradykinin and possible bradykinin, both of which bind to bradykinin receptors and induce vasodilation, lung injury, and inflammation. It is well kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Angioedema has been hypothesized to favor COVID-19 progression, and in turn COVID-19 can further exacerbate pre-existing angioedema condition. 35 Therefore, people with T2D who were using ARBs might essentially be at higher risk for developing critical conditions related to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Angioedema has been hypothesized to favor COVID-19 progression, and in turn COVID-19 can further exacerbate pre-existing angioedema condition. 35 Therefore, people with T2D who were using ARBs might essentially be at higher risk for developing critical conditions related to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 8, further network-based drug repurposing is calculated and novel and potent drugs targeting SARS-CoV-2 are identified. For instance, danazol (antigonadotropic and anti-estrogen) was discovered in our study and other in silico drug screening studies as a repurposable candidate with demonstrated immunomodulatory properties mediating the attenuation of TNFα-induced IL-8 overexpression [97,98]. Additionally, danazol has been shown to be a candidate agent affecting essential pathways involved in SARS-CoV-2 pathogenesis, including mRNA splicing and ubiquitin-mediated proteolysis pathways [98].…”
Section: Discussionmentioning
confidence: 66%
“…For instance, danazol (antigonadotropic and anti-estrogen) was discovered in our study and other in silico drug screening studies as a repurposable candidate with demonstrated immunomodulatory properties mediating the attenuation of TNFα-induced IL-8 overexpression [97,98]. Additionally, danazol has been shown to be a candidate agent affecting essential pathways involved in SARS-CoV-2 pathogenesis, including mRNA splicing and ubiquitin-mediated proteolysis pathways [98]. As androgens could be suspected as playing a crucial role in driving both specific SARS-CoV-2 entry receptors' overexpression and anti-viral immune response suppression, therapeutic interventions with danazol must only be administered with great caution and complete consideration [99].…”
Section: Discussionmentioning
confidence: 75%
“…Coagulation and brinolytic pathways are also regulated by C1-INH and it is presumed that the lower C1-INH activity could predispose to more severe SARS-CoV-2 infection 24 . Moreover, C1-INH has been demonstrated to interact with components of the extracellular matrix, leading to the hypothesis that these components concentrate C1-INH at the local site of in ammation in order to regulate complement and contact systems 25 .…”
Section: Discussionmentioning
confidence: 99%
“…This effect could contribute to attacks in patients with both HAE-C1-INH and HAE-nC1-INH. In addition, the loss of inhibitory activities of C1-INH would be expected to enhance complement activation together with microvascular injury, leading to worse evolution of SARS-CoV-2 infection 25 .…”
Section: Discussionmentioning
confidence: 99%